An overview on preparation of emulsion-filled gels and emulsion particulate gels. (April 2019) - Farjami, Toktam; Madadlou, Ashkan
Abstract: Background: Emulsion gels are a class of soft solid-like materials. These composite materials are structurally either a polymeric gel matrix into which emulsion droplets are incorporated (emulsion-filled gels), or a network of aggregated emulsion droplets (emulsion particulate gels). Emulsion gels are increasingly used in pharmaceutics, cosmetics and food industries. Scope and approach: This article reviews fabrication methods of emulsion gels, and describes factors that influence gel properties and functionality. Effect of polymer-surfactant interactions on the rheology of emulsion gel systems is explained. Then, irreversible and reversible clustering of oil droplets as the basis of making emulsion particulate gels is deliberated. Key Findings and Conclusions: Oil droplets depending on their interfacial composition act as either active or inactive fillers in an emulsion-filled gel. Actively functioning oil droplets can increase gel modulus, whereas, inactive oil droplets typically weaken gel texture. Interactions between surfactants and polymers, which influences filler affinity to gel matrix, have significant consequences on emulsion gel rheology. For protein-based emulsion gels, surfactant may also influence proteins unfolding and aggregation. In situ gelation of an emulsion can be triggered by environmental factors such as temperature changes during processing and storage or by physiological stimuli such as acidic pH in the stomach. The clustering approach, which is used to form emulsion particulate gels may be utilized to control digestibility of lipids in the gastrointestinal tract. The capability of encapsulating two or more different lipophilic components within a single delivery system may be achieved via heteroaggregation technique. Graphical abstract: Image 1 Highlights: Emulsion gel is a composite structure consisting of oil droplets within a gel matrix. They can be categorized as emulsion-filled gels and emulsion particulate gels. Oil droplets may act as active fillers and influence emulsion-filled gel rheology. Surfactant-polymer interactions can affect the affinity of filler to gel matrix. Particles deformability and interactions between them influence particle gel rheology.